Pengaruh Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) Terhadap Efektivitas, Kinerja Pengguna Dan Dampak Pada Kualitas Laporan Keuangan Balai Guru Penggerak Indonesia Timur - Rinna Rinna; Rusman Soleman; Suwito Suwito (Universitas Katolik Widya Karya Malang, 2024)
The purpose of this study is to determine the effect of the implementation of institution-level financial application systems on effectiveness, user performance and impact on the quality of financial statements. This type of research uses causal explanatory research methods with a quantitative approach. The data collection technique in this study was carried out by distributing questionnaires in the form of google forms with a 5-point likert scale. The analysis tool used in this study used SmartPLS. The results of this study show that: 1). The implementation of SAKTI affects user effectiveness; 2). The implementation of SAKTI affects user performance; 3). The implementation of SAKTI does not affect the quality of financial statements; 4). User effectiveness affects the quality of financial statements; 5). User performance has no effect on the quality of financial statements.